Comparative Analysis of the Complete Chloroplast Genomes of Five Quercus Species - Yang, Yanci; Zhou, Tao; Duan, Dong; Yang, Jia; Feng, Li; Zhao, Guifang (Frontiers in Plant Science, 2016)
Quercus is considered economically and ecologically one of the most important genera in the Northern Hemisphere. Oaks are taxonomically perplexing because of shared interspecific morphological traits and intraspecific morphological variation, which are mainly attributed to hybridization. Universal plastid markers cannot provide a sufficient number of variable sites to explore the phylogeny of this genus, and chloroplast genome-scale data have proven to be useful in resolving intractable phylogenetic relationships. In this study, the complete chloroplast genomes of four Quercus species were sequenced, and one published chloroplast genome of Quercus baronii was retrieved for comparative analyses. The five chloroplast genomes ranged from 161,072 bp (Q. baronii) to 161,237 bp (Q. dolicholepis) in length, and their gene organization and order, and GC content, were similar to those of other Fagaceae species. We analyzed nucleotide substitutions, indels, and repeats in the chloroplast genomes, and found 19 relatively highly variable regions that will potentially provide plastid markers for further taxonomic and phylogenetic studies within Quercus. We observed that four genes (ndhA, ndhK, petA, and ycf1) were subject to positive selection. The phylogenetic relationships of the Quercus species inferred from the chloroplast genomes obtained moderate-to-high support, indicating that chloroplast genome data may be useful in resolving relationships in this genus.